Anthropometric and physical performance characteristics of Colombian elite male wrestlers - Ramirez Vélez, R.; Argothy, R.; Meneses Echavez, J.; Sánchez Puccini, M. B.; Lopez Alban, C. A.; Cohen, D. D. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
Aim: The objective of the present study was to evaluate anthropometric and physical performance characteristics of elite male wrestlers. Methods: The Colombian Wrestling Team was evaluated while in preparation for the Olympic Games (n=21, age 27.9±6.7 years). Athletes were tested on anthropometric and fitness parameters: body composition, somatotype distribution according to Heath-Carter, aerobic capacity, vertical jump, and anaerobic power. Results: The results in mean±SD and (95%CI) showed a percentage of body fat 13.6±3.0 (95%CI 12.2 to 15.0); muscle mass 46.4±2.2; (95%CI 45.4 to 47.4); ponderal index 41.0±1.8 (95%CI 40.2 to 41.8); body adiposity index (BAI) 25.1±3.6 (95%CI 23.5 to 26.8) and somatotype distribution mesomorphic-ectomorph (5.3-1.6-3.8). Mean aerobic capacity was 45.9±6.6 (9%CI 42.8 to 48.9 ml/kg/min), vertical jump was 36.4±6.6 (95%CI 11.8 to 16.6 cm) and anaerobic power was 92.6±19.5 (95% CI 83.7 to 101.5 kg/s). Conclusion: These results may provide a profile of elite wrestlers that can be used as training targets for developing athletes. The results may also provide information for training and tactical emphases.